2011
DOI: 10.1603/en11110
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the Structure of Suburban Ant (Hymenoptera: Formicidae) Communities and the Abundance of Tapinoma sessile

Abstract: Urbanization can alter the organization of ant communities and affect populations of urban pest ants. In this study, we sampled ant communities in urban and suburban yards to understand the habitat factors that shape these communities and influence the abundance of a common pest species, Tapinoma sessile (Say). We used pitfall traps to sample ant communities and a combination of pitfall traps and baiting to collect T. sessile at 24 sites in Knoxville, TN. In total, we collected 46 ant species. Ant species ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…The remaining area was covered by a monoculture of grass to create lawns. Previous studies show that the percentage canopy cover is an important factor influencing ant species richness [37][38], [41], [61]. A study by [24] demonstrated that land development can significantly affect ant diversity, even in areas that retain a substantial component of native vegetation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining area was covered by a monoculture of grass to create lawns. Previous studies show that the percentage canopy cover is an important factor influencing ant species richness [37][38], [41], [61]. A study by [24] demonstrated that land development can significantly affect ant diversity, even in areas that retain a substantial component of native vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Doing so requires long-term observations to document temporal changes in species inventories over time, and such data is logistically difficult to obtain and typically unavailable. As a result, the impact of urbanization is typically inferred indirectly by comparing species diversity along spatial gradients, typically by examining diversity along urban-rural gradients at a single time point [24], [27], [35], [41]. Urban-rural gradient studies are clearly a simplification of the complex patterns produced by urbanization [42].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows that high biodiversity is a barrier against invasions [49] and this theory could explain why T. sessile does not flourish into supercolonies within natural habitats. The odorous house ant is in the minority of species capable of tolerating urbanization [26] , [50] , and likely upon release from competitive species or natural habitat constraints capitalizes on vacant niches and becomes established as a dominant urban pest [26] , [51] and an invasive species [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, harbours are a major introduction pathway (O'Connor & Weston, 2010), especially of ants (Suarez, McGlynn & Tsutsui, 2010). Yet studies of ant communities in urban ecosystems are rare (but see Lessard & Buddle, 2005;Toennisson, Sanders & Klingeman, 2011). In Denmark, 80% of foreign trade goes through Danish industrial harbours (Danske Havne, 2017).…”
Section: Introductionmentioning
confidence: 99%